2020
DOI: 10.1002/chem.202000674
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Heterocycles through Denitrogenative Cyclization of Triazoles and Benzotriazoles

Abstract: During the past few decades, there has been considerable growth in the development of denitrogenative reactions of triazole skeletons to construct valuable cyclic compounds, particularly heterocycles. Despite the inherent difficulty of the ring‐opening of triazole derivatives, many novel and efficient approaches have arisen in this area mainly with the use of transition metal (such as rhodium, palladium, silver, copper) catalysis, photolysis, or free radical mediated reactions. Generally, these procedures begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 138 publications
0
24
0
Order By: Relevance
“…1,2,3-Triazoles containing electron-withdrawing groups on N(1), such as sulfonyl, fluoroalkyl, or 1,2,4-triazolyl, easily available via copper­(I)-catalyzed azide–alkyne cycloaddition, are heterocycles that are widely utilized in organic synthesis . Since the discovery of rhodium-catalyzed reactions of N -sulfonyl triazoles in 2008 involving α-imino rhodium carbenoids 3 as reactive intermediates, these transformations of N -sulfonyl- and N -fluoroalkyl-1,2,3-triazoles have been widely used in the synthesis of a wide array of nitrogen-containing compounds (Figure A). Recently, we have showcased a new type of reactivity specific to N -fluoroalkyl-1,2,3-triazoles in the presence of strong Brønsted or Lewis acids . In comparison to rhodium-catalyzed reactions utilizing heating-induced ring opening and rhodium carbene formation, acid-mediated transformations proceed via protonation or coordination of N(1) on the triazole ring leading to diazonium salt 5 , which upon nitrogen elimination forms vinyl cation 6 .…”
mentioning
confidence: 99%
“…1,2,3-Triazoles containing electron-withdrawing groups on N(1), such as sulfonyl, fluoroalkyl, or 1,2,4-triazolyl, easily available via copper­(I)-catalyzed azide–alkyne cycloaddition, are heterocycles that are widely utilized in organic synthesis . Since the discovery of rhodium-catalyzed reactions of N -sulfonyl triazoles in 2008 involving α-imino rhodium carbenoids 3 as reactive intermediates, these transformations of N -sulfonyl- and N -fluoroalkyl-1,2,3-triazoles have been widely used in the synthesis of a wide array of nitrogen-containing compounds (Figure A). Recently, we have showcased a new type of reactivity specific to N -fluoroalkyl-1,2,3-triazoles in the presence of strong Brønsted or Lewis acids . In comparison to rhodium-catalyzed reactions utilizing heating-induced ring opening and rhodium carbene formation, acid-mediated transformations proceed via protonation or coordination of N(1) on the triazole ring leading to diazonium salt 5 , which upon nitrogen elimination forms vinyl cation 6 .…”
mentioning
confidence: 99%
“…Although the aforementioned reactions are considered as the most important transition-metal catalyses, a plethora of vital reactions can be effectively catalyzed by various transition metals including reductive elimination, oxidative addition, and transmetallation. Transition metal catalysis has also found extensive applications in the convenient and efficient synthesis of a wide variety of heterocyclic systems (Ma et al, 2017 ; Ramanathan and Liu, 2017 ; Tiwari and Bhanage, 2017 ; Chatterjee et al, 2018 ; Saikia et al, 2018 ; Chen et al, 2020 ; Debabrata et al, 2020 ; Ghosh et al, 2020 ; Janardhanan et al, 2020 ; Jiang et al, 2020 ; Kanwal et al, 2020 ; Kojima and Matsunaga, 2020 ; Li and Zhang, 2020 ; Nagata and Obora, 2020 ; Neto and Zeni, 2020a , b ; Pal et al, 2020 ; Ratmanova et al, 2020 ; Sahiba and Agarwal, 2020 ; Sonawane et al, 2020 ; Xuan et al, 2020 ). However, the literature survey revealed only an example of zinc (Shi et al, 2004 ), a limited number of iron-catalyzed (Melvin et al, 1992 ; Valderrama et al, 1999 ; Kanth et al, 2006 ; Yin et al, 2012 ; Gopalaiah et al, 2017 , 2019 ; Raut and Bhanage, 2017 ; Eidi et al, 2018 ), and relatively more copper-catalyzed reactions, leading to the synthesis of quinazoline and quinazolinone derivatives (Melvin et al, 1992 ; Chatterjee et al, 2018 ; Potuganti et al, 2018 ; Liang et al, 2019 ; Rodrigues et al, 2019 ; Donthiboina et al, 2020 ).…”
Section: Synthesis Of Quinazolinone Derivativesmentioning
confidence: 99%
“…Benzotriazoles are used in numerous synthetic reactions, where they can act as leaving groups, electron donors, electron withdrawers, and radical or carbanion precursors. Denitrogenative cyclization is of particular interest for the synthesis of heterocycles. Computational investigations of the denitrogenation of benzotriazole 1 at the CASPT2 level of theory demonstrated that nitrogen loss from the initially formed diazo valence tautomer 2 results in 1,3-diradical/carbene 3a/3b , which has a triplet ground state, but a low-lying open-shell singlet state is responsible for further reactions. , This diradical/carbene can cyclize to benzazirine 4 , the formation of which has been demonstrated experimentally by carbon labeling, and the aza-Wolff rearrangement to fulvenimine 5 followed by tautomerization yields 1-cyanocyclopentadiene 6 in high yield (Scheme ).…”
Section: Introductionmentioning
confidence: 99%